2021
DOI: 10.1002/cssc.202002594
|View full text |Cite
|
Sign up to set email alerts
|

Direct Deoxydehydration of Cyclic trans‐Diol Substrates: An Experimental and Computational Study of the Reaction Mechanism of Vanadium(V)‐based Catalysis**

Abstract: The deoxydehydration of carbohydrates represents a key target to leverage renewable biomass resources chemically. Using a vanadium(V)‐based catalyst, it was possible to directly deoxydehydrate cyclic trans‐diol substrates. Accompanying mechanistic characterisation of this process by density functional calculations pointed to an energetically tractable route for deoxydehydration of cyclic trans‐diol substrates involving stepwise cleavage of the diol C−O bonds via the triplet state; experimentally, this was supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…While exploring the inhibition of reactivity by ring strain, Bryce and coworkers found that alkene yields were substantially lower in the absence of ambient light. 15 Intersystem crossing events and stepwise olefin extrusion have been previously explored and are supported by DFT 16 but explicit enhancement of yield by light are shown here. The yields of cyclic cis and trans diols were still low (<20%), but enhancements of up to 5× were observed for reactions performed in light versus dark conditions.…”
mentioning
confidence: 61%
“…While exploring the inhibition of reactivity by ring strain, Bryce and coworkers found that alkene yields were substantially lower in the absence of ambient light. 15 Intersystem crossing events and stepwise olefin extrusion have been previously explored and are supported by DFT 16 but explicit enhancement of yield by light are shown here. The yields of cyclic cis and trans diols were still low (<20%), but enhancements of up to 5× were observed for reactions performed in light versus dark conditions.…”
mentioning
confidence: 61%
“…Reactions for upgrading biobased polyhydroxylated compounds by the selective removal of hydroxy groups are of great interest, for example, in deoxydehydration, [133][134][135][136][137] hydrodeoxygenation, [138,139] didehydroxylation, [140] or dehydrative epoxidation [141] of vicinal diols. While impressive advances have been achieved with various chemocatalysts, both transition metalbased and metal-free, further research and development is clearly needed for improving the selectivity, outcome, and sustainability of these reactions, such as high-performing, stable, and sustainable catalysts, additives, and solvents, in order to design industrially viable biobased processes.…”
Section: Emerging Biocatalytic O-defunctionalization Reactionsmentioning
confidence: 99%
“…The proposed cycle involved several spin crossovers and consisted of diolate formation, reduction by triphenylphosphane, formation of a metallacycle and cleavage. Aksanoglu et al 160 revisited [VO 2 (dipic)] − -catalyzed DODH. At the M06-L/SDD/6-311+G**/SMD level, they found the barrier for reaction initiation by diolate formation to be 96 kJ mol −1 lower than that for initiation by reduction.…”
Section: Deoxydehydration Kinetics and Mechanismmentioning
confidence: 99%
“…Recently, Aksanoglu et al 160 compared yields obtained in the dark and in the presence of visible light under exclusion of UV light by the use of borosilicate glass. They found a [ n -Bu 4 N]V(dipic)O 2 catalyst to give consistently higher olefin yields in the presence of light.…”
Section: Process Aspects: Phase Chemistry Separations Reactor Choice ...mentioning
confidence: 99%